Sosialisasi dan Pelatihan Budidaya Maggot untuk Pengelolaan Sampah Organik dan Pakan Ternak di Dukuh Sutorejo - Condro W; Tasya D P; Firdausii K; Nabila N; Salindri B C; Isro Nur S K; Faris Yasin R; Muhammad Rizal E; Muhammad Dewa P; Nur Oktavia N H; Mohammad Ariel S R (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Household waste management is a significant challenge in Indonesia along with population growth and economic activity. In 2021, organic waste contributed 54.31% of the total waste in Surabaya. One innovative solution is the use of bioconversion technology with Black Soldier Fly (BSF) larvae which can decompose organic waste quickly and produce animal feed and organic fertilizer. The socialization and training program in Dukuh Sutorejo aims to introduce and train residents in maggot cultivation as an alternative for waste management and animal feed. This activity includes socialization about the benefits of maggots, training in cultivation techniques, and providing maggot samples for independent cultivation. The evaluation results showed that 91% of participants understood how to apply maggots for organic waste management and animal feed, indicating the success of the program.